Pregnancy-associated thrombotic thrombocytopenic purpura - Gerth, Jens; Schleussner, Ekkehard; Kentouche, Karim; Busch, Martin; Seifert, Mandy; Wolf, Gunter (Thrombosis and Haemostasis, 2009)
Thrombocytopenia during pregnancy is a common diagnostic and management problem. Several differential diagnosis must be considered including manifestations of thrombotic thrombocytopenic purpura (TTP). We report here on a case of a 21-year-old pregnant woman who presented initially severe thrombocytopenia (8 Gpt/l) in the 20th+1 week of gestation. The patient had an antibody against ADAMTS13, and enzyme activity was <5%. Immediate plasmapheresis treatment was initiated, followed by plasma infusions, and again plasmapheresis. A male neonate was delivered by caesarean section in the 32nd week of gestation. The child had an uncomplicated postnatal development. After delivery, the mother’s platelet count and ADAMTS13 activity increased to normal values. This case shows interesting aspects of TTP in pregnancy and a close cooperation between obstetricians, nephrologists and pediatricians is necessary for a successful outcome of the pregnancy.
Keywords: Thrombotic thrombocytopenic purpura; pregnancy; ADAMTS 13; von Willebrand factor; plasmapheresis; thrombocytopenia